Measuring Space and Furniture Occupancy in Academic Libraries: From Data Gathering to Visualization. Issue 6 (18th August 2019) - Castro, Rodrigo; Spina, Carli; Xu, Yaqing (Allison)
Abstract: Academic libraries are a vital space for collaboration, socialization, research, and quiet study. To support these needs, they must offer a variety of environments, noise levels, and furniture to support varying student needs. However, it can be difficult to understand these specific needs and properly balance the types of spaces and seating alternatives to optimally meet them. This article describes a space usage study undertaken to determine patron needs and preferences and the resulting visualization of the data using Tableau Public. The project provided important insights into patron space preferences and use, and the methodology can be replicated at other institutions.